HYPERHOMOCYSTEINEMIA IN CIRRHOSIS OF THE LIVER - Juraev Bobur Rakhmonovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Numerous clinical and epidemiological studies have identified elevated plasma homocysteine levels as a risk factor for atherosclerotic vascular diseases and thromboembolism. Hyperhomocysteinemia may develop due to defects in genes that metabolize homocysteine; dietary conditions that lead to a deficiency of vitamins B6, B12, or folic acid; or chronic alcohol use. Homocysteine is an intermediate product of methionine metabolism, which occurs mainly in the liver. Impaired liver function leads to changes in the metabolism of methionine and homocysteine; however, the molecular basis of such changes is not fully understood. In addition, the mechanisms of cellular toxicity caused by homocysteineare not fully defined.